1994
DOI: 10.1017/s031716710004124x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine and Selegiline – Lack of Significant Interaction

Abstract: The use of the combination of fluoxetine, an anti-depressant serotonin uptake inhibitor, and selegiline, a monoamine oxidase -B inhibitor, was reviewed in a large population of patients with Parkinson's disease. All records were reviewed from a Parkinson's disease clinic to determine how many patients were treated simultaneously with selegiline and fluoxetine. Patient characteristics, duration and dose of treatment, side effects and reasons for discontinuation were noted. Twenty-three patients received both me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…However, the combination of fluoxetine and selegiline in PD patients appears to be generally safe and well tolerated. Thus, in a series of 23 PD patients taking the two drugs concomitantly, no adverse effects other than those associated with each of the two drugs taken individually were reported [222]. …”
Section: Sert Inhibitorsmentioning
confidence: 99%
“…However, the combination of fluoxetine and selegiline in PD patients appears to be generally safe and well tolerated. Thus, in a series of 23 PD patients taking the two drugs concomitantly, no adverse effects other than those associated with each of the two drugs taken individually were reported [222]. …”
Section: Sert Inhibitorsmentioning
confidence: 99%
“…Originally described in patients taking nonselective MAO inhibitors,73 it is now most commonly seen in patients taking more than one drug with serotonergic activity (often selective serotonin reuptake inhibitors [SSRIs] or tricyclic antidepressants in combination with MAO inhibitors) 74. Treatment generally consists of supportive care and discontinuing the offending agent 75. Though serotonin syndrome is potentially quite dangerous, there does not appear to be a serious risk of developing it while taking selective MAO-B at PD doses, even when taking an SSRI as well.…”
Section: Safety Of Mao-b Inhibitorsmentioning
confidence: 99%
“…Though serotonin syndrome is potentially quite dangerous, there does not appear to be a serious risk of developing it while taking selective MAO-B at PD doses, even when taking an SSRI as well. Two retrospective studies have failed to show evidence of serotonin syndrome in patients taking selegiline and an SSRI 75,76. A survey of members of the Parkinson Study Group found 4568 PD patients treated with a combination of selegiline and an SSRI.…”
Section: Safety Of Mao-b Inhibitorsmentioning
confidence: 99%
“…Many patients with PD suffer from concurrent mood disorders, including depression and anxiety (Lauterbach 2004), and therefore use of SSRIs and other antidepressants in this population is common. The possibility of interactions arising as a result of use of selective MAOIs in conjunction with SSRIs, tricyclic, or other antidepressant medications in PD has been raised by several investigators (Suchowersky and deVries 1990;Blackwell 1991;Ritter and Alexander 1997), although careful retrospective studies of selegiline use have failed to fi nd such an interaction (Waters 1994;Toyama and Iacono 1994;Richard et al 1997). The TEMPO trial allowed limited use of amitriptyline, paroxetine, sertraline, and trazodone, and both amitriptyline and trazodone were allowed in the LARGO study at low and stable doses.…”
Section: Potential Medication Interactionsmentioning
confidence: 99%